SOME ASPECTS OF FORMING OF THE MODERN FIELD OF INTERSUBJECTIVE - Донченко, О. А. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
Intersubjectivizm we understand as a structure of individual psychological fractal, in which it touches to all meaningful external. In modern analytical psychology (Stoloroou, Brandshaft, Dg. Atvoud ect) of intersubjective study in a role of the intersubjective field as central explanatory construction in a psychoanalytic theory and practice. In the article we examine the meaningful aspects of modern psyhoculture.